Ceramic material porous structure prepared using pore-forming additives - Mocciaro, Anabella (2017)
Porous ceramic materials exhibit high permeability, specific surface, and thermal shock resistance, and therefore they may be used successfully in the production of filters, membranes, and as a substrate for catalytic reactions, etc. One method for preparing high material porosity is addition of a pore-forming substance. Porosity (open and closed), pore size distribution, their size and shape, depend on the nature, amount, and morphology of pore-forming substance. In this article the effect is elucidated of three different types of carbon additives on porosity of ceramic prepared from clay and chemical binder precursor. Carbon materials are studied in an x-ray diffractometer. Ceramic material properties are studied using a mercury porosimeter, the Archimedes method, scanning electron and optical microscopes, and microcomputer tomography.